PEMETAAN PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 1 KOTA MOJOKERTO - VITA NURMAYASARI (Jurnal Pendidikan Akuntansi (JPAK), 2013)
Limitations of the media provided by the school become the burdens for the teachers to deliver lesson to the students. Based on the research can be concluded as follow: (1) PowerPoint as media used by the teacher for class XI in SMAN 1 Mojokerto City because it consdred quite attractive for the students and the teacher masters the media; (2) the result of the study has been examined by the expert and it determined that this media is fleksible to be used as the media for teaching accounting and it was indicated by the percentage 72,14% with a basic competency categories to make a decent overview of accounting cycle of service and 69,29% with category for basic competency the company financial reporting service; and (3) the responses of students to the use of media PowerPoint is very well and it’s demonstrated by the results of student questionaires with 78,13% for both categories of basic competency to make an overview of the accounting cycle and 82,15% service company with basic competency categories for company financial reporting services. Keywords: Instructional Media, Accounting Lesson